Edward R. Murrow and the Birth of broadcast journalism - Edwards, Bob (Wiley, 2004)
Edwards, former host of NPR's Morning Edition, brings perspective and knowledge to this memoir of radio and television legend Edward R. Murrow. The author chronicles Murrow's innovations in radio and television broadcasting, including live radio reports of the war in progress in Europe in 1940; exposure of the despotism of Senator Joseph McCarthy on CBS in 1953; the powerful television documentary Harvest of Shame on the deplorable conditions of migrant workers in the U.S.; and the first in-depth television news program, See It Now. Drawing on actual broadcasts and conversations with Murrow's colleagues, including Edward Bliss Jr., who wrote for Murrow at CBS and was later the first editor of The CBS Evening News with Walter Cronkite, Edwards brings to life the early days of radio and television and the innovations that Murrow sparked. In the afterword, Edwards analyzes the decline in broadcast news since Murrow's pioneering days. Readers